(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Non Orthogonal Multiple Access (NOMA) is new significant research area, as it gives novel idea of multiplexing the communication channels on the same frequency and time slot , which can present revolutionary outcomes. The general idea of (NOMA) is based on using Successive Interface Cancelling (SIC) , where each user of the channel is distinguished by its unique power level, and then all the users are modulated/demodulated in certain order. In this study, many experiments are run to examine NOMA with digital modulation schemes, such as ASK, PSK, FSK, QPSK, and 8 QAM. MATLAB codes are built to perform each experiment. According to the performed simulation, 8-QAM has the lowest Bit Error Rate (BER).